Kejujuran dalam Perspektif Hadis : Kajian terhadap Peran Kejujuran dalam Membangun Karakter Muslim dalam Kehidupan Sehari-hari - Rian Aldiansyah; Badrudin Badrudin (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Honesty (ṣidq) is a core value in Islamic teachings that not only shapes individual behavior but also plays a vital role in establishing a just, trustworthy, and moral society. In various authentic hadiths, the Prophet Muhammad ﷺ emphasized that honesty leads to righteousness (al-birr), and righteousness leads to Paradise. Conversely, lying leads to wickedness and Hell, and is one of the signs of hypocrisy. This study aims to explore the significance of honesty in Islam based on the Prophet’s hadiths and the explanations of classical scholars. The research method used is qualitative with a library research approach. Primary data sources include authentic hadith compilations such as Sahih al-Bukhari and Sahih Muslim, while secondary data are drawn from relevant scholarly literature. The analysis applies a thematic approach by grouping hadiths on honesty into sub-themes and interpreting their contexts and meanings. The findings show that honesty must be cultivated continuously, is a sign of true faith, and a condition for attaining divine blessings in all aspects of life, including economic transactions (mu‘āmalāt). Scholars such as Imam al-Nawawī, Ibn Rajab, and Ibn Ḥajar unanimously affirm that honesty is the root of all virtue and a source of spiritual light. Thus, honesty in Islam is not merely a social ethic but a spiritual path to divine pleasure and salvation in both this world and the hereafter. The analysis follows a thematic approach, categorizing the hadiths related to honesty into sub-themes and interpreting their contexts and deeper meanings. The findings emphasize that honesty is an essential part of true faith, continuously cultivated by believers, and a necessary condition for receiving divine blessings in all areas of life, including economic transactions (mu‘āmalāt). Scholars like Imam al-Nawawī, Ibn Rajab, and Ibn Ḥajar unanimously assert that honesty is the foundation of all virtues and a source of spiritual enlightenment. Therefore, in Islam, honesty is more than just a social ethic; it is a spiritual path that leads to divine pleasure and salvation in this life and the hereafter. This study underscores the central role of honesty in both personal morality and broader social harmony within Islamic teachings.